Application of Topical Immunotherapy in the Treatment of Alopecia Areata: A Review and Update - Mahasaksiri T; Kositkuljorn C; Anuntrangsee T; Suchonwanit P (Dove Medical Press, 2021)
Thipprapai Mahasaksiri, Chaninan Kositkuljorn, Tanaporn Anuntrangsee, Poonkiat Suchonwanit Division of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Poonkiat SuchonwanitDivision of Dermatology, Department of Medicine, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, 270 Rama VI Road, Ratchathewi, Bangkok, 10400, ThailandTel +66 2-2011141Fax +66 2-201-1211 Ext 4Email poonkiat@hotmail.comAbstract: Treatment of extensive or recalcitrant alopecia areata (AA) is a major clinical challenge. Even after thorough investigation of several medications, its treatment outcomes have remained unsatisfactory. While there is no US Food and Drug Administration-approved medication for AA yet, topical immunotherapy has been a well-documented treatment option. Dinitrochlorobenzene, squaric acid dibutylester, and diphenylcyclopropenone are three substances that have demonstrated efficacy in the treatment of extensive or recalcitrant AA. Despite being commonly used, the mechanism underlying topical immunotherapy is not well-elucidated and a wide range of clinical efficacies have been reported in the literature. The aim of this review was to summarize and update the pharmacology, mechanism of action, therapeutic efficacy, and tolerability of topical immunotherapy in the treatment of AA.Keywords: contact sensitizers, dinitrochlorobenzene, diphencyprone, diphenylcyclopropenone, hair loss, squaric acid dibutylester